Sex and control : veneral disease, colonial physicians, and indigenous agency in German colonialism, 1884-1914 /: veneral disease, colonial physicians, and indigenous agency in German colonialism, 1884-1914. (2015) - Walther, Daniel Joseph, 1965-
No abstract available